Audit Sistem Informasi Aplikasi Fingerprint Menggunakan Cobit 5 - Diaul Munir; Eva Zuraidah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The existence of information technology is able to support organizations in providing accurate, relevant, fast information. By harmonizing organizational goals, organizational information systems/information technology can speed up the process of achieving organizational goals, but of course supervision and maintenance are needed so that the organization's IS/IT runs well. Information technology audit is a form of operational audit, but information technology audit whose main objective is to improve IT governance, operational audit of information resource management, effectiveness, efficiency, economics of the information system functional unit. Based on the identification of the problems that have been described, this research will discuss the calculation of the capability level in the fingerprint attendance application in the Honda Pandawa Lima Sejati work environment. :DSS 01(manage operations ), DSS03 (manage problem) The results of research on auditing information systems for fingerprint attendance applications using the COBIT 5 domain DSS 01 and DSS 03 framework, it can be concluded that auditing information systems Fingerprint at Pandawa Lima Dealers Using COBIT 5 has almost reached the expected target level, the results of data processing of the distribution of questionnaires into data obtained and the rating to level F has fulfilled, the scale of rounding off the capability model condition index is at level 4 of the company